Fenomena Tradisi Puasa Nisfu Sya’ban Lingkungan Delapan Kelurahan Binjai Serbangan Kecamatan Air Joman Kabupaten Asahan (Studi Living Hadis - Nasution, Sulthoni Karim (UIN Sumatera Utara Medan, 2024)
The tradition of Ni¡fu Sha'ban fasting has long been rooted in Indonesian society, although there are questions among the ulama regarding the validity of the hadiths that form the basis of this practice. This phenomenon reflects the dynamics of Islam in Indonesia which combines